ANALISIS TINGKAT KESEHATAN TANAMAN PADI SAWAH BERBASIS PENGOLAHAN CITRA DIGITAL - HASAN, ASMAR; TAUFIK, MUHAMMAD; SABARIA, WA ODE; BANDE, LA ODE SANTIAJI; ASNIAH, ASNIAH; ARINI, RIAN (Jurnal Agroteknos, 2024)
Rice is the main food crop in Indonesia, and plant health greatly affects production. Farmers in Lebo Jaya Village, Konda Subdistrict, South Konawe Regency, still use traditional cultivation techniques such as scattered planting systems and minimal liming and intensive fertilization, resulting in low levels of rice plant health. Digital image processing technology offers a more efficient and accurate alternative in diagnosing plant health compared to traditional methods. This study aims to evaluate the differences in the health level of paddy rice plants using different planting systems and cultivation technology inputs in Lebo Jaya Village based on digital image processing. The methods used include field surveys, recording, and image processing of rice plants of the Inpari 32, Ciliwung, and Inpari 33 varieties managed by farmers and HKTI-Sultra (Association of Indonesian Farmers Harmony-Southeast Sulawesi). The results showed that rice plants managed by HKTI-Sultra with a more advanced planting system and cultivation technology inputs had a higher level of health compared to rice plants managed by local farmers. Digital image processing technology proved effective in detecting and evaluating the health of rice plants based on differences in cultivation systems.